2010
DOI: 10.1016/j.eneco.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Oil price shocks and their short- and long-term effects on the Chinese economy

Abstract: A considerable body of economic literature shows the adverse economic impacts of oil-price shocks for the developed economies. However, there has been a lack of empirical study of this kind on China and other developing countries. This paper attempts to fill this gap by answering how and to what extent oil-price shocks impact China's economy, emphasizing on the price transmission mechanisms. To that end, we develop a structural vector auto-regressive model. Our results show that an oil-price increase negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(157 citation statements)
references
References 24 publications
7
147
1
2
Order By: Relevance
“…An increase in the oil price would negatively affect the investment and output in China (Tang et al, 2010). Second, oil price shocks can result in changes in unemployment rates.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…An increase in the oil price would negatively affect the investment and output in China (Tang et al, 2010). Second, oil price shocks can result in changes in unemployment rates.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Tang et al [67] confirmed that oil price fluctuation could cause short-term output decline from reduced capacity utilization rate and have a long-term effect on output through the price/monetary transmission mechanism. Additionally, these adverse effects of oil price shock could be transmitted from producer to end-user.…”
Section: Oil Price Volatilitymentioning
confidence: 95%
“…In the Eleventh Five-Year Plan from 2006-2010 and Twelfth Five-Year Plan from 2011-2015, the government set the goal of reducing energy intensity by 20% in 2010 relative to 2005 and 16% in 2015 relative to 2010 [90]. Although oil consumption per unit economic output has declined over recent decades, it is still much higher than developed countries in absolute terms [67]. Therefore, as shown in Fig.…”
Section: Improving Energy Efficiencymentioning
confidence: 98%
“…Many studies related to oil price in China are focused on the macroeconomic effects of oil price shocks, and many empirical researches support that there exists a strong relationship between oil price shock and the macroeconomy in China [3,[31][32][33][34]. Zhao et al [35] established a dynamic stochastic general equilibrium (DSGE) model and found that oil supply shocks mainly produced shorter effects on China's output and inflation, and demand shocks that were specific to the crude oil market contributed the most to the fluctuations in China's output and inflation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To ensure sound and rapid economic growth, it is vital for China to implement the oil reform program cautiously. As we all know, oil is the blood of industrial development and a sharp fluctuation on oil prices will affect economic development [3]. Therefore, the Chinese government (National Development and Reform Commission) has been in charge of oil price reform from 2003 to now.…”
Section: Introductionmentioning
confidence: 99%